The Role of Islamic Banking in Achieving Sustainable Development Goals (SDGs) in West Sumatera - Dewi, Sandra; ., Yaswirman; Febriamansyah, Rudi; ., Henmaidi (Journal of Ecohumanism, 2024)
Bukittinggi is a tourist city that shows the potential of MSMEs for the community, but capital problems still constrain them from establishing MSMEs. Therefore, murabahah and mudharabah financing distributed by BSI KCP Bukittinggi has a role in supporting MSME activities. This study aims to determine the role of Islamic banking in achieving sustainable development in West Sumatra. Using a researcher-determined descriptive qualitative research approach, this study describes Islamic banking's involvement in reaching SDG 1 (no poverty) in Bukittinggi City, West Sumatra Province, in great detail. This study's findings point to the importance of Islamic banking in Achieving Sustainable Development in West Sumatra through the distribution of financing to the community, namely murabahah financing and mudharabah financing, will encourage regional economic movement, especially for MSME actors in Bukittinggi City.